The Intensity of Ethnic Chinese Political Communication on Active Political Participation in DKI Jakarta - Ilman Heriyawan; Muhammad Aksal; Kevin Gustilanti Marrel (HISTORICAL: Journal of History and Social Sciences, 2024)
Exploring the complexity of the political landscape in Jakarta influenced by ethnic diversity, with a focus on the significant role of the Chinese ethnic group in political dynamics. Starting from the foundation of ethnic diversity, the aim is to investigate the intensity of political communication within the Chinese ethnic group and its impact on public perception and political participation in Jakarta. Understanding the dynamics of political communication becomes increasingly crucial, especially in the context of the potential for the government and politicians to leverage these opportunities through appropriate approaches, creating a multicultural political contestation. This approach requires an understanding of various aspects, including intercultural communication, communication psychology, and the media's impact on policies.This research specifically explores public perception of political communication within the Chinese ethnic group, uncovering how political messages are understood by Jakarta's diverse society across different social and ethnic layers. The analysis encompasses levels of political participation, including participation in general elections and contributions to political organizations. To address the complexity, this research analyzes factors influencing political communication within the Chinese ethnic group, including social, cultural, economic, and political aspects, to understand the context shaping their political messages.Despite facing challenges in obtaining credible data, this research is expected to provide practical insights for the Chinese ethnic group, the government, and the general public in designing inclusive communication strategies and strengthening social harmony in Jakarta